Achieving an excellent combination of strength and ductility in a single-phase metastable medium-entropy alloy - Caixia Wang; Ruixing Sheng; Dawei Zhou; Weidong Li; Shuying Chen; Fanchao Meng; Gihan Velisa; Daiyi Chao; Liang Jiang; Peter K. Liaw; Yang Tong (Journal of Materials Research and Technology, 2023)
The development of robust alloys capable of maintaining high strength and ductility at cryogenic temperatures has been a long-sought goal, particularly for load-bearing applications in extremely low-temperature environments. In this study, we reported a newly developed face-centered-cubic (FCC) metastable (Ni0·3Co0·4Cr0.3)94Mo6 medium-entropy alloy (Mo-MEA) with an excellent synergy of strength and ductility at 77 K, surpassing the toughest equiatomic NiCoCr MEA. Compared to the equiatomic NiCoCr MEA, the Mo-MEA exhibited a substantial increase in yield strength by 68 % (from 407 to 685 MPa) and a decent enhancement of the ultimate tensile strength by 10 % (from 1289 to 1415 MPa), along with a marginal increase in elongation from 75 % to 78.45 %. Electron backscatter diffraction and transmission electron microscopy revealed the activation of multimodal deformation mechanisms, including dislocations, stacking faults, twinning, and FCC-to-hexagonal-close-packed phase transformation, during the tensile deformation at 77 K.